LEARNING OUTCOMES IN THE STUDY CONTRIBUTION OF LEARNING STYLE AND EMOTIONAL INTELLIGENCE ON STUDENTAKIDAH AKHLAQ AT MTS. DARUL QUR’AN DELI SERDANG DISTRICT - Robiatul Adawiyah Sihombing (Universitas Islam Negeri Sumatera Utara Medan, 2019)
This study aims to determine the contribution of learning styles andemotional intelligence to student learning outcomes. This study usescorrelational statistics with 98 respondents in Deli Serdang Regency.Learning style data collection, emotional intelligence throughquestionnaires. While the learning outcomes data obtained through reportcards. Data were analyzed using simple correlation techniques, regression, multiple correlation and partial correlation. The findings of the study are there are positive contributions between: (1) learning styles towardslearning outcomes with ry1 of 0.430 with a regression equation Ý = 34.149+ 0.773 X1, (2) Emotional intelligence on learning outcomes with ry2 of0.515 regression equation Ý = 59.607+ 0.463 X2 and (3) learning styles andemotional intelligence together towards the learning outcomes with ry12of 0.628 with regression Ý = 194.566 + 0.826X1 + 0.236X2. The magnitude ofthe partial correlation of learning styles (X1) to learning outcomes (Y) ifemotional intelligence (X2) is in a constant state is 0.437. The partialcorrelation of emotional intelligence (X2) to learning outcomes (Y) if thelearning style (X1) is constant at 0.520. The results of this study concludedthat the higher the learning style and emotional intelligence, the higher thelearning outcomes of students at MTs. Daarul Qur'an Deli SerdangRegency.